A novel copyright marking approach using steganography and robust RSA asymmetric-key cryptographic technique in audio files. (17th November 2017) - Srinivasan, Kathiravan; Gowthaman, T.; Kanakaraj, J.
Abstract: Information hiding techniques have recently become important in a number of application areas. Digital audio, video, and pictures are increasingly furnished with distinguishing but imperceptible marks, which may contain a hidden copyright notice or serial number. This paper presents a novel approach of Copyright marking using steganography and strong RSA Asymmetric-key cryptographic technique in audio files. The audio with secret information is indiscernible to human ear. The owner of the file is only aware of the secret key to access his information in the file. Thus making the method more secure and robust to the Intentional attacks.